Management of Mukhadushika with Ayurvedic Line of Treatment (AYUSHDHARA, 2022)
The concept of beauty is as old as mankind and civilization. A good complexion is desirable and decisive component of the beauty so everyone wants to be attain good complexion and good look so in Mukhadushika there is altered face complexion as a result of Shalmali kanta sadrusha pidaka over the face which is due to vitiation of Kapha and Vatadosha and Ashrayi of Raka dhatu as it is a disease of adolescence age due to hormonal imbalance and can be correlate to the acne vulgaris. Treating this acne in the initial stage itself makes easier and doesn’t leave of any scars, which mentally depresses individual and face insecure so in Ayurveda different treatment modalities are explained to treat the Mukhadushika so we are taken Jaloukavacharna among the treatment with some Shamanoushadi to see the result.